Trade Balance and Pakistan Economy using ARDL model: A Perspective of Trade Deficit Developing Economies - Hanif, Sana; Fatima, Syeda Neha; Iqbal, Muhammad shahid; Hanif, Salman; Batool, Sania (iRASD Journal of Economics, 2023)
The influence of trade balance on the economy provides opportunities and challenges against an ongoing global uncertain environment. Existing studies take a broad picture to analyze such influence, often failing under specific implications, indicating a need for a close perspective. Taking this background, this paper aims to study the main features of the complex association between trade balance and economic growth through a close perspective of Pakistan. Accordingly, the study follows econometric techniques and applies the autoregressive distributed lag (ARDL) model on time series days of Pakistan from 1970-2021. In methodology, various statistical techniques are applied to refine the findings, mainly unit-root analysis and cointegration modeling in both long and short-run evaluations. In addition, dependence on trade balance was measured against independence of currency rate, joblessness, investment, and overall domestic production. Findings revealed that the local currency rate, in the long run, has a negative and significant association with the trade deficit, suggesting a growth in exports by lowering that rate. It also boosts local manufacturing to compete against imports, which feel costly. These results can facilitate customizing the local policy guidelines at the national level or in developing countries with similar financial issues like trade deficits. This study’s implications suggest that a close viewpoint between trade balance and the economy could guide in pursuing area-specific goals on a sustainable basis.